Analisis Beban Industri pada Penyulang Kima di PT. PLN (Persero) ULP Daya UP3 Makassar Utara - Suryani Suryani; Muhammad Sukri Zaenal; Abdul Hafid (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Energy Electricity is something that is needed in people's lives, the need for electrical energy is increasing. the need for electrical energy is increasing. demand for electrical energy continues to increase along with economic growth and community welfare. the welfare of society. The growth in demand for electrical energy is influenced by the development of the growing manufacturing and industrial sectors. This study aims to determine the energy imbalance between the industrial and general power lines on the reliability of the 20 kV network. Methods research methods used in this study are primary and secondary research. secondary research. The results obtained in this study are the imbalance of load on the 20 kV power load on the 20 kV industrial repeater transformer power at the time of high loading during the day is 192.4633333 A with a percentage of the power of the 20 kV network. day 192.4633333 A with a percentage of 0.556252408 % and the lowest general repeater load of 68.45 A with a load percentage of 0. %percentage of 0.197919075%.